2022
DOI: 10.3390/galaxies10010008
|View full text |Cite
|
Sign up to set email alerts
|

Mass Ratio and Spot Parameter Estimation from Eclipsing Binary Star Light Curves

Abstract: Eclipsing binary stars have a rich history of contributing to the field of stellar astrophysics. Most of the available information on the fundamental properties of stars has come from the analysis of observations of binaries. The availability of powerful computers and sophisticated codes that apply physical models has resulted in determinations of masses and radii of sufficient accuracy to provide critical tests of theories of stellar structure and evolution. Despite their sophistication, these codes still req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The relationship between the mean residual and mass ratio q is shown in Figure 1. It is clearly seen that all the q − search curves have very deep and sharp minima, indicating very precise mass ratio can be obtained (e.g., Zhang et al 2017;Li et al 2019Li et al , 2021bTerrell 2022). The mass ratio corresponding to the minimum of the mean residual was chosen as the initial value and an adjustable parameter, new solutions were started to obtain a convergent result, then the errors of mass ratio can be determined.…”
Section: Light-curve Investigationmentioning
confidence: 99%
“…The relationship between the mean residual and mass ratio q is shown in Figure 1. It is clearly seen that all the q − search curves have very deep and sharp minima, indicating very precise mass ratio can be obtained (e.g., Zhang et al 2017;Li et al 2019Li et al , 2021bTerrell 2022). The mass ratio corresponding to the minimum of the mean residual was chosen as the initial value and an adjustable parameter, new solutions were started to obtain a convergent result, then the errors of mass ratio can be determined.…”
Section: Light-curve Investigationmentioning
confidence: 99%
“…Terrell & Wilson (2005) showed that the photometric mass ratio for semi-detached and over-contact binaries is often overestimated for partial eclipses. Recently Terrell (2022) noted that not properly modeled third light will lead to mass ratios that are too low. Our solution of RU UMi show no third light and no total eclipses on the LCs (just like other stars).…”
Section: Discussionmentioning
confidence: 99%
“…We considered this model as the underlying model that can describe the system and explored the LC solution of our 2016 data with a spotted model using a GA optimizer. The GAs show promise for determining spot parameters from a simultaneous solution of LCs with broad wavelength coverage (Terrell 2022). To investigate spot parameters, the PHOEBE program was interfaced with PIKAIA.…”
Section: Lc Modelingmentioning
confidence: 99%